Retroperitoneal Endometrioid Carcinoma Arising from Ureteral Endometriosis - Daiken Osaku; Fuminori Taniguchi; Maako Moriyama; Shinya Sato; Tetsuro Oishi; Tasuku Harada (Case Reports in Obstetrics and Gynecology)
Primary ureteral endometriosis is considered to be an uncommon form with an incidence of less than 0.1% in endometriosis. We reported a case of retroperitoneal endometrioid carcinoma possibly arising from ureteral endometriosis. A 52-year-old woman complained left backache. A solid mass in left retroperitoneal cavity with hydronephrosis was found. Diagnostic laparotomy with bilateral salpingo-oophorectomy and biopsy of the mass were performed. Although the primary lesion was not defined in the surgery, the histopathological diagnosis of specimen was endometrioid carcinoma. In the interval debulking surgery after the chemotherapy, tumor adjacent the left iliac vessels was observed. We resected the mass together with 5 cm left ureter and performed ureterectomy and anastomosis. The patient was diagnosed as the malignant transformation of ureteral endometriosis. Adjuvant chemotherapy is now undergoing. In case of finding the cancer tissue in women, we should take into account the malignant transformation of less common endometriosis, including ureteral endometriosis.